FRI0010 Pharmacokinetics, Safety and Tolerance of BCD-085, A Novel IL-17 Inhibitor, Based on The Results of Phase 1 Clinical Study in Healthy Volunteers. (15th July 2016) - Chernyaeva, E.; Eremeeva, A.; Galustyan, A.; Ivanov, R.
Abstract : Background: BCD-085 is an innovative humanized monoclonal antibody against interleukin-17 with genetically modified Fc- and CDR-regions, aimed to improve treatment outcomes in patients with several autoimmune disorders. Objectives: To study pharmacokinetics and safety of a single SC injection of BCD-085 in ascending doses in healthy male volunteers. Methods: A standard "3+3" first-in-human dose escalation phase 1 clinical study design was used. Different cohorts of healthy male volunteers 18 to 45 years of age received a single subcutaneous injection of BCD-085 in ascending doses (0.05 mg/kg, 0.025 mg/kg, 0.0825 mg/kg, 1.25 mg/kg, 1.75 mg/kg, 2.25 mg/kg and 3.0 mg/kg). After injection all participants underwent 57 days of observation which included assessment of the tolerance, safety, pharmacokinetics and immunogenicity of the studied medicine. Results: 22 healthy male volunteers received a single SC injection of BCD-085. Pharmacokinetics: Pharmacokinetic data were available from 21 volunteers with median body weights of 73.6 kg (range; 65.2–84.8). 1 volunteer withdrew from the study due to SAE that was not related to study drug (car accident). Regardless of the cohort changes of BCD-085 concentration were linear: after SC injection it slowly increased and reached the maximum value at the end of the first week. Thus, dose dependency was observed, while the half-life was not dependent on the dose and was 15–22 days. Mean Cmax of BCD-085 amounted to 12, 232.5 ng/ml (median – 10937.0 ng/ml), Tmax – 156.6 hours (median 168.0), AUC0-t – 8780483.5 (ng/ml)*h (median – 8169096.2 (ng/ml)*hr), AUC0-inf – 4786108616.7 (ng/ml)*h (median – 4275500952.5 (ng/ml)*h), the half-life – 387.9 hours (median – 383.7 hours). Safety: In total, 6 adverse events were registered during the study, the toxicity in all these cases was mild (grade 1 in accordance with CTCAE v.4.03). Transaminases increase was more common (9.09%); grade 1 neutropenia occurred just in one volunteer. Single SC injections of BCD-085 were well tolerated with no signs of any local reactions. Immunogenicity assessment did not detect occurrence of anti-drug antibodies. Conclusions: BCD-085 is safe when administered SC in a wide range of doses from 0.05 to 3.0 mg/kg. Pharmacokinetics of a novel IL-17 blocker is standard for therapeutic monoclonal antibodies. Further clinical evaluation of BCD-085 is underway. References: final study report on phase 1 clinical study of BCD-085 in healthy volunteers. Disclosure of Interest: E. Chernyaeva Employee of: BIOCAD, A. Eremeeva Employee of: BIOCAD, A. Galustyan Grant/research support from: BIOCAD, R. Ivanov Employee of: BIOCAD